Colour of paradise. - Majidi, Majid, 1959-; Mahjoub, Hossein; Ramezani, Mohsen; Feyzi, Salameh; Safari, Farahnaz; Kohandairy, Alireza; Davudi, Mohammad; Hassandoost, Hassan (Varohar Film Co., 2011)
The tale of an eight-year-old blind boy whose father sees him as a hindrance. Young Mohammed is blind but has acute hearing: his receptiveness is in contrast with his father, a widower, who wishes to offload him to prevent the boy standing in the way of his planned marriage. The Color of Paradise is a painfully beautiful film about a blind boy's ability to see more than others who are bound by tradition and religion. Filmed with mainly amateur actors, this is an award winning and critically acclaimed film. Awards: Best Film and Best Actor at Cinemanila (Philippines) International Film in 2000; Festival Best Film, Best Director, Best Actor at Valenciennes (France) Film Festival in 2000; Best Director at Isfahan Children and Young Adults Film Festival in 2000; Best Film at Fajr (Tehran) International Film Festival in 1999; Grand Prix Americas Award for Best Film at Montreal World Film Festival in 1999.